Fractal Growth of a Conventional Calamitic Liquid Crystal - CHAN, HO-KEI (My University, 2004)
We report observation of liquid crystal phase ordering via fractal growth aggregates for a calamitic, non-bent-core mesogen. Fractal growth of a conventional smectic-C (Sm-C) phase from the isotropic melt after a temperature quench was experimentally investigated with respect to time, cell gap, quench depth, and quench rate. The determined fractal dimensions relating to the area as well as the perimeter of the growing aggregates suggest a phase formation process via a percolation mechanism. Computer simulations of the phase ordering process give further evidence for percolation growth, qualitatively reproducing the observed textures and quantitatively leading to the same fractal dimensions. We propose a general model of fractal smectic liquid crystal growth, which accounts for all of the different systems observed so far, bent-core or ?banana? phases as well as the observation of fractal phase ordering of a conventional Sm-C phase. The model is based on the ?breaking? of the commonly observed growth anisotropy by strong in-layer molecular interactions. These are provided by hydrogen bonding in the Sm-C case discussed here and by steric interactions in the case of the bent-core phases discussed in previous publications.
PUBLISHED
This paper presents a detailed comparison between simulated percolation clusters and the experimental fractal-like aggregates of a growing hydrogen-bonded liquid crystal phase. It presents strong evidence that the intriguing fractal growth behaviour observed for several liquid crystal phases is generally based on a percolation mechanism.
Keywords: Physics